Implementation of Marketing Communication on MSME Business Strategies during the Covid-19 Pandemic - Kumba Digdowiseiso; Hamrin Hamrin (Budapest International Research and Critics University, 2022)
This research was conducted to determine the implementation of marketing communications on the implementation of MSME business strategies during the Covid-19 pandemic. The research method used is descriptive qualitative method. The results obtained from this research show that the strategies that can be applied by MSMEs are to change the form of marketing to online or e-commerce, carry out digital sales and create branding to advertise their products, improve product and service quality for convenience and create bonds with residents. Marketing communications and strategies that can be applied by SMEs are changing the form of marketing from conventional to online or e-commerce, implementing digital sales and creating branding to advertise their products.